Start order and medal outcomes: An analysis of apparatus finals in men’s artistic gymnastics - Chih-Yu Chen; Kuang-Hui Chen; Kang-Hao Lu (PLoS ONE, 2026)
Purpose This study examined the relationship between start order and competition outcomes in men’s artistic gymnastics apparatus finals. Methods Competition outcomes from three Olympic Games and nine World Championships were analyzed. Ordinal-based analyses, including Spearman’s rank-order correlation and Kendall’s tau-b, were conducted to examine the relationship between start order and final rankings. Logistic regression was used to assess the association between start order and medal attainment. In addition, Mann–Whitney U tests were used to compare final rankings between start-order groups; independent-samples t -tests were used to assess differences in Difficulty (D) scores, Execution (E) scores, and total scores; and Chi-square tests were used to evaluate associations between start-order grouping, medal attainment, and continental affiliation. Results Ordinal correlation and logistic regression analyses showed no significant associations between start order and final rankings or medal attainment across apparatuses. Start-order grouping had limited influence on final rankings across most apparatuses. A significant effect was observed only in the pommel horse, where second-half gymnasts achieved higher E-scores and won more medals. Medal distributions between European and non-European athletes were similar across apparatuses and start-order groupings. Conclusion Overall, start-order grouping had minimal effects. However, pommel horse results highlight the importance of execution stability. The findings support the general fairness of the current judging system and Code of Points. Future research should examine warm-up procedures under revised FIG regulations and extend analyses to women’s artistic gymnastics.